2019
DOI: 10.1080/09243453.2019.1618348
|View full text |Cite
|
Sign up to set email alerts
|

Home learning environment across time: the role of early years HLE and background in predicting HLE at later ages

Abstract: This study explores how various measures of home learning environment (HLE) collected at different ages are related to each other and explores associations when the effects of significant child and family characteristics are controlled for. Different age appropriate measures of the HLE were constructed at ages 3, 7, 11, and 14. The measures were derived from parents' reports (3, 7, and 11), but at age 14 both adolescents' self-reports and parents' questionnaires responses were used. Multilevel models tested th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 39 publications
0
26
1
2
Order By: Relevance
“…Further, we did not have a measure of the home language and communication environment during the primary school years, nor ongoing measures of SES. These factors have been shown to be influential beyond the early years, as family circumstances can change for many reasons (Jeynes, 2002;Toth et al, 2020). In addition to this, the sample size for the measurement of social adjustment at school entry was much lower than that for literacy skills.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Further, we did not have a measure of the home language and communication environment during the primary school years, nor ongoing measures of SES. These factors have been shown to be influential beyond the early years, as family circumstances can change for many reasons (Jeynes, 2002;Toth et al, 2020). In addition to this, the sample size for the measurement of social adjustment at school entry was much lower than that for literacy skills.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Concurrently, suboptimal home environment can adversely impact child development and behaviours (Grandjean & Landrigan, 2006; Shonkoff, Garner, Siegel, et al, 2012). Home learning environments have been serially evaluated and are found to be associated with the baseline home learning environment status (Toth et al, 2020) and can affect language and cognitive development in children (Rodriguez & Tamis‐LeMonda, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Focusing on the first years of life, the family is seen as the most important learning environment ( Bornstein, 2002 ) and parenting behavior has been emphasized as particularly important for the development of children (e.g., NICHD Early Child Care Research Network, 2002a , b ). Further, research showed that the early home learning environment also predicts the quality of the later home learning environment ( Toth et al, 2020 ). According to the educational framework of the home learning environment (e.g., Kluczniok et al, 2013 ), structural characteristics such as parental education, occupation, and household income [as indicators of the socioeconomic status (SES) of the family] affect educational processes (e.g., quality of interaction behavior, joint activities).…”
Section: Introductionmentioning
confidence: 99%